2021
DOI: 10.14309/ajg.0000000000001554
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Cold Snare Polypectomy Technique: Technique Matters More Than Snare Wire Diameter

Abstract: INTRODUCTION: Cold snare polypectomy (CSP) is safe and effective for the removal of small adenomas (≤10 mm); however, reported incomplete resection rates (IRRs) vary. The optimal CSP technique, where a wide margin of normal tissue is resected around the target lesion, and snare design have both been hypothesized to reduce the IRR after CSP. We sought to investigate the efficacy of a thin-wire versus thick-wire diameter snare on IRR, using the standardized CSP technique. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
59
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 40 publications
2
59
1
Order By: Relevance
“…On the other hand, Sidhu et al, while performing a multicenter study to compare the use of thin- and thick-wire snares for CSP in small (≤ 10 mm) colorectal polyps, reported that the overall IRR of the cohort was only 1.5 %. There was no significant difference in the IRR between the thin- and thick-wire arms 6 .…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…On the other hand, Sidhu et al, while performing a multicenter study to compare the use of thin- and thick-wire snares for CSP in small (≤ 10 mm) colorectal polyps, reported that the overall IRR of the cohort was only 1.5 %. There was no significant difference in the IRR between the thin- and thick-wire arms 6 .…”
mentioning
confidence: 69%
“…What is important for endoscopists is to be mindful of the finer aspects of the CSP technique. These details include the following: (i) careful ascertainment of the lateral margins, especially for a flat lesion, including the use of image-enhanced endoscopy if necessary; (ii) ensuring that a 2-mm rim of normal mucosa is captured consistently prior to resection; (iii) maximization of snare pressure on the mucosal surface by applying firm downward pressure on the mucosa with the snare using the up/down wheel of the endoscope; (iv) slow closure of the snare to ensure adequate seating of the snare into the normal mucosa surrounding the polyp, in order avoid the snare slipping over the normal mucosa upon completion of snare closure; (v) careful examination of the mucosal defect and its edges post-resection to detect any residual lesions and allow repeated resection until complete endoscopic resection is achieved [6].…”
mentioning
confidence: 99%
“…One view suggested that the residual polyps after CSP were mainly caused by vertical margin unevaluable/positive because of shallower excision depth compared with hot snare polypectomy and endoscopic mucosal resection. Indirect signs showed in this study such as obtaining more submucosal tissue on the stump and leaving less frequent cold snare defeat protrusions at the ulcer bed might cue the better performance of thin-wire snare regarding resection depth to some extent (1). As the presence of submucosal tissue and complete absence of muscularis mucosa (MM) were both infrequent, it is challenging to find a good measure reflecting the whole picture of deep resection margins when the efficacy of different snares is compared.…”
mentioning
confidence: 90%
“…To clarify for the authors of this letter, as described in the methods section of our manuscript, we performed marginal biopsies of all resected lesions in our study, to assess for incomplete resection (2). However, the authors have failed to realize that we are the first study in the published literature that used a standardized approach to cold snare resection, commencing at the point of resection (with a wide margin of normal mucosa captured around the target lesion) to defect inspection.…”
mentioning
confidence: 99%
“…By ensuring that a margin of normal tissue was resected around the target site, the assessment of IRR using marginal biopsies is less prone to issues of sampling error. In addition, the use of the water jet, to evert the defect edges—as shown in Figures 2 and 3 of the published article—allows for systematic endoscopic evaluation at the defect margins for residual adenomatous tissue (2). These important tenets of the cold snare resection technique were unique to this study.…”
mentioning
confidence: 99%